Enhancing student achievement: Developing a Differentiated Instruction Formative Assessment Model (DIFAM) - Muh. Asriadi AM; Samsul Hadi; Edi Istiyono; Anna Isabela Sanam; Jumriani Sultan; Gulzhaina K. Kassymova (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2025)
An ideal assessment should offer constructive feedback and insights into students' strengths and weaknesses in learning. This study aims to develop an assessment model integrating formative assessment with Differentiated Instruction (DIFAM) to assess learning achievements proportionally. The DIFAM model was developed using the ADDIE development framework. The research sample consisted of 99 students from four high schools in Bandung Regency. Student learning profiles were analyzed using N-Gain and paired sample t-test. Data analysis was conducted with R Studio and JASP software. Data analysis using the N-Gain formula revealed an average improvement in student learning achievements of 25% with the implementation of DIFAM. The formative tests conducted over eight sessions showed that students grasped the material more effectively compared to conventional teaching methods. Feedback from students and teachers indicated that DIFAM facilitated more structured learning and provided constructive feedback, contributing significantly to enhanced student performance. The DIFAM model demonstrates its ability to cater to diverse student needs, achieve significant learning improvements, and has the potential for broader application to ensure more inclusive and equitable learning outcomes.